Tindak Ilokusi Dalam Komedi Situasi Preman Pensiun (epsd. 73) - Prapti Wigati Purwaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2015)
This tendency draws interest to find the speech act classification and the meaning of it. This paper is using dialog script of Preman Pensiun part 73 written by Aris Nugraha. In this analysis the writer  uses speech act theory by Searl, and pragmatic theory by Austin. From the data source the writer found 45 data. Based on the analysis are there are 5 speech act classification, representatives, commisive, expressive, directive, and declarative. Directive speech act command and request is mostly used by the characters in the situation comedy series Preman Pensiun. The conclusion of this analyasis are the writer found 3 data  for representative (2 suggest and 1 swear), 3 data for commisive, 26 data for request (20 command and 6 request), 13 data for expressive (2 thank, 10 complaint, 1apologize), and 1 data for declare.